Terahertz transitions in carbon nanotubes and graphene nanoribbons - Saroka, V. A. (Animo Repository, 2017)
Interband dipole transitions are calculated in quasi-metallic single-walled carbon nan-otubes and armchair graphene nanoribbons. It is shown that the curvature effects for tubes and the edge effects for ribbons result not only in a small band gap opening, corresponding to THz frequencies, but also in a significant enhancement of the transition probability rate across the band gap. This makes these nanostructures perspective canditates for sources and detectors of THz radiation. © 2017 IEEE.